Knee cartilage morphologic characteristics and muscle status of professional weight lifters and sprinters: A magnetic resonance imaging study - Gratzke, C.; Hudelmaier, M.; Hitzl, W.; Glaser, C.; Eckstein, F. (The American Journal of Sports Medicine, 2007)
Whereas muscle and bone mass have been shown to strongly depend on mechanical stimulation (loading history), this relationship has not been established for articular cartilage.